Pengaruh Harga, Kualitas Produk, dan Promosi Terhadap Keputusan Pembelian Pada Konsumen Produk Nivea di Sidoarjo - Mita Trias Putri Prastianti; Siti Aisah (Journal of Creative Power and Ambition (JCPA), 2024)
This research wants to find out more about "The Influence of Price, Product Quality and Promotion on Purchasing Decisions of Nivea Product Consumers in Sidoarjo". The background for conducting this research is that there are many cosmetic brands competing to create beauty products with quality that guarantees consumers to make repeat purchases. The aim of this research is this research aims to determine together the influence of price (X1), product quality (X2), promotion (X3) on purchasing decisions (Y) for Nivea products. The research method used in sampling was a purposive sampling method with 100 respondents. The respondents of this research are consumers who have used Nivea products in the city of Sidoarjo. The instrument tests used in this research are Validity Test, Reliability Test, Multiple Linear Regression Analysis, T Test, F Test, and Determination. The research results show that price influences purchasing decisions, product quality influences purchasing decisions, and promotion influences purchasing decisions. Product quality has the most dominant influence on purchasing decisions.